Umifenovir treatment is not associated with improved outcomes in patients with coronavirus disease 2019: a retrospective study. (July 2020) - Lian, N.; Xie, H.; Lin, S.; Huang, J.; Zhao, J.; Lin, Q.
Abstract: Objectives: Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Umifenovir (Arbidol®) is an antiviral drug being used to treat influenza in Russia and China. This study aimed to investigate the effectiveness and safety of umifenovir for COVID-19. Methods: A retrospective study was performed in a non-intensive care unit (ICU) ward in Jinyintan Hospital from 2 February 2020 to 20 March 2020. COVID-19 was confirmed by real-time reverse-transcriptase polymerase chain reaction (RT-PCR) assay of pharyngeal swab specimens. The confirmed patients were divided into the umifenovir group and the control group according to the use of umifenovir. The main outcomes were the rate of negative pharyngeal swab tests for SARS-CoV-2 within 1 week after admission and the time for the virus to turn negative. The negativity time of SARS-CoV-2 was defined as the first day of a negative test if the nucleic acid of SARS-CoV-2 was negative for two consecutive tests. Results: A total of 81 COVID-19 patients were included, with 45 in the umifenovir group and 36 in the control group. Baseline clinical and laboratory characteristics were comparable between the two groups. Thirty-three out of 45 (73%) patients in the umifenovir group tested negative for SARS-CoV-2 within 7 days after admission, the number was 28/36 (78%) in the control group (p 0.19). The median time from onset of symptoms to SARS-CoV-2 turning negative was 18 days (interquartile range (IQR) 12–21) in the umifenovir group and 16 days (IQR 11–21) in the control group (p 0.42). Patients in the umifenovir group had a longer hospital stay than patients in the control group (13 days (IQR 9–17) vs 11 days (IQR 9–14), p 0.04). No deaths or severe adverse reactions were found in both groups. Discussion: Umifenovir might not improve the prognosis or accelerate SARS-CoV-2 clearance in non-ICU patients. A randomized control clinical trial is needed to assess the efficacy of umifenovir.